2023
DOI: 10.26599/tst.2022.9010015
|View full text |Cite
|
Sign up to set email alerts
|

An ANN-Based Short-Term Temperature Forecast Model for Mass Concrete Cooling Control

Abstract: Concrete temperature control during dam construction (e.g., concrete placement and curing) is important for cracking prevention. In this study, a short-term temperature forecast model for mass concrete cooling control is developed using artificial neural networks (ANN). The development workflow for the forecast model consists of data integration, data preprocessing, model construction, and model application. More than 80 000 monitoring samples are collected by the developed intelligent cooling control system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Owing to advancements in information technology, closed-loop control technology has been implemented in various construction sites [35]. For example, for intelligent pipe-cooling control in massive concrete [36], a short-term temperature forecast model for mass concrete cooling control was developed using ANN [37]. An intelligent grouting control system named the intelligent grout control hub (iGH) has been established to achieve one-button closed-loop intelligent control of cement grouting by developing robust grouting control models, novel grouting facilities, and intelligent online monitoring approaches [38].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to advancements in information technology, closed-loop control technology has been implemented in various construction sites [35]. For example, for intelligent pipe-cooling control in massive concrete [36], a short-term temperature forecast model for mass concrete cooling control was developed using ANN [37]. An intelligent grouting control system named the intelligent grout control hub (iGH) has been established to achieve one-button closed-loop intelligent control of cement grouting by developing robust grouting control models, novel grouting facilities, and intelligent online monitoring approaches [38].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the turbulent airflow field around trees has been widely simulated using computational fluid dynamics (CFD) technology. Due to the complex morphological structure of trees, previous studies have simplified tree canopies into elliptical, square, rectangular and other geometries and equated them to porous media to analyze the effect of trees on the flow field [27][28][29]. It has been shown that the porosity is not constant during the flow of air [30][31][32].…”
Section: Introductionmentioning
confidence: 99%